Performance Assessment of Patient on Dialysis - Fabio Manfredini; Nicola Lamberti (Karger Publishers, 2014)
Patients on dialysis are poorly active and show a low level of physical functioning. Questionnaires and objective measurements of spontaneous physical activity are available as well as complex-expensive or simple-unexpensive tests useful to assess the patient's exercise capacity. Performance assessment unravels patients' capabilities, enables a tailored exercise prescription and provides predictive information on main clinical outcomes and therefore this topic should be of interest for nephrologists. A routinary minimal pool of tests might be usefully performed in a dialysis centre to stratify the patient's risk and to recognize patients in need of exercise training in order to address them to community-based or rehabilitative programs.